2020
DOI: 10.1029/2019jd032058
|View full text |Cite
|
Sign up to set email alerts
|

Potential Effect of Halogens on Atmospheric Oxidation and Air Quality in China

Abstract: Air pollution has been a hazard in China over recent decades threatening the health of half a billion people. Much effort has been devoted to mitigating air pollution in China leading to a significant reduction in primary pollutants emissions from 2013 to 2017, while a continuously worsening trend of surface ozone (O 3 , a secondary pollutant and greenhouse gas) was observed over the same period. Atmospheric oxidation, dominated by daytime reactions involving hydroxyl radicals (OH), is the critical process to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 105 publications
4
52
0
Order By: Relevance
“…More discussion of the mechanisms for ozone increase is in Text S6 (He et al, 2017; Jin & Holloway, 2015; Li et al, 2018; Lu et al, 2019; Wang et al, 2017). It is worth noting that recent findings suggest halogen chemistry (not included in our model) could to some extent affect the responses of oxidants to NO x reductions (Li, Badia, et al, 2020; Saiz‐Lopez & von Glasow, 2012; Simpson et al, 2015), but should not change our conclusion regarding the trends of oxidants (see more in Text S7) (Chen et al, 2017, 2018; Fu et al, 2018; Jin & Chu, 2006; Li, Badia, et al, 2020; Liu & Abbatt, 2020; Sarwar et al, 2007; Wang et al, 2016; Wang, Chen, et al, 2019; Wang, Jacob, et al, 2019; Xing et al, 2019; Yarwood et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…More discussion of the mechanisms for ozone increase is in Text S6 (He et al, 2017; Jin & Holloway, 2015; Li et al, 2018; Lu et al, 2019; Wang et al, 2017). It is worth noting that recent findings suggest halogen chemistry (not included in our model) could to some extent affect the responses of oxidants to NO x reductions (Li, Badia, et al, 2020; Saiz‐Lopez & von Glasow, 2012; Simpson et al, 2015), but should not change our conclusion regarding the trends of oxidants (see more in Text S7) (Chen et al, 2017, 2018; Fu et al, 2018; Jin & Chu, 2006; Li, Badia, et al, 2020; Liu & Abbatt, 2020; Sarwar et al, 2007; Wang et al, 2016; Wang, Chen, et al, 2019; Wang, Jacob, et al, 2019; Xing et al, 2019; Yarwood et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…More modeling has focused on the regional impacts of Cl and ClONO 2 (see Section 5.1). Accounting for the chemistry associated with these molecules can lead to increases of 3%-5% in surface ozone in the United States (Sarwar et al, 2012) and significant regional enhancements elsewhere in the NH, particularly over China (Sarwar et al, 2014;Li et al, 2020), with smaller increases over Europe (Sherwen et al, 2017b).…”
Section: Cycle 1 (R17mentioning
confidence: 99%
“…Sarwar et al (2019) conducted a year-long simulation in 2006 of CMAQ and reported a decrease of 25% over oceanic waters and >6 ppbv in the present study domain. Li, Badia, Wang, et al (2020) employed the WRF-Chem model to report 4%-10% reduction in surface O 3 along the coast in summer 2018 due to the addition of halogen sources and chemistry in China.…”
Section: 1029/2020jd034175mentioning
confidence: 99%
“…A follow-up work by Stone et al (2018) found an increase of OH (∼2%) and a decrease of HO 2 (-5% to -2%) for the year 2009 in East Asia. Li, Badia, Wang, et al (2020) utilized the WRF-Chem model in China and reported changes of OH and HO 2 in between -10% and 20% in summer 2018 along the coast. Note that Li, Badia, Wang, et al (2020) included anthropogenic chlorine emission over land for their simulation, which led to an increase of both OH and HO 2 in polluted coastal regions.…”
Section: Impact Of Halogens On Free Radicalsmentioning
confidence: 99%
See 1 more Smart Citation